Chemically Modified SDF-1α mRNA Promotes Random Flap Survival by Activating the SDF-1α/CXCR4 Axis in Rats - Luo, Zucheng; Bian, Yujie; Zheng, Gang; Wang, Huijing; Yan, Bingqian; Su, Wenting; Dong, Wei; Hu, Zhichao; Ding, Jian; Wang, Anyuan; Li, Shi; Fu, Wei; et al. (Frontiers in Cell and Developmental Biology, 2021)
Random skin flaps are frequently applied in plastic and reconstructive surgery for patients suffering from soft tissue defects caused by congenital deformities, trauma and tumor resection. However, ischemia and necrosis in distal parts of random skin flaps remains a common challenge that limits the clinical application of this procedure. Recently, chemically modified mRNA (modRNA) was found to have great therapeutic potential. Here, we explored the potential of fibroblasts engineered to express modified mRNAs encoding the stromal cell-derived factor-1α (SDF-1α) to improve vascularization and survival of therapeutic random skin flaps. Our study showed that ﬁbroblasts pre-treated with SDF-1α modRNA have the potential to salvage ischemic skin flaps. Through a detailed analysis, we revealed that a ﬁbroblast SDF-1α modRNA combinatorial treatment dramatically reduced tissue necrosis and signiﬁcantly promoted neovascularization in random skin flaps compared to that in the control and vehicle groups. Moreover, SDF-1α modRNA transcription in ﬁbroblasts promoted activation of the SDF-1α/CXCR4 pathway, with concomitant inactivation of the MEK/ERK, PI3K/AKT and JAK2/STAT3 signaling pathways, indicating a possible correlation with cell proliferation and migration. Therefore, ﬁbroblast-mediated SDF-1α modRNA expression represents a promising strategy for random skin flap regeneration.